Struktur Biaya dan Pendapatan Usaha Ternak Ayam Ras Pedaging Pola Kemitraan di Provinsi Jambi - Akbar, Wahyu; Hidayat, Nia Kurniawati; Sehabudin, Ujang (Universitas Batanghari Jambi, 2024)
This research aims to determine the cost structure, revenue, income and R/C ratio of broiler chicken farming businesses. The analysis method used is quantitative (cost structure analysis, income, R/C ratio and difference test). The research results show that PT X shows better cost efficiency than PT Y, this is reflected in the higher R/C ratio. This indicates that PT X is able to manage production costs more effectively, through negotiating better prices for feed or using more efficient technology. PT X results of the difference test using the Mann Whitney Test show that the two companies have significantly different revenues. PT X and PT Y still have the potential to improve performance. PT Y can learn from PT X best practices in managing costs and increasing revenue.